Adult male coatis play with a band of juveniles - Logan,CJ (2013)
This study examined the play behaviour in one group of coatis (Nasua narica) at La Selva Biological Station in Costa Rica. We incidentally found adult males playing with juvenile coatis, and conducted post-hoc analyses to investigate this interaction. Coati groups consist of adult females and juveniles of both sexes until male juveniles reach two years of age and leave the band to become solitary. Adult males only tolerate juveniles for a brief period during breeding season when the males court females to mate. Outside of the breeding season, adult males are known to prey on juveniles. In this study, when adult males were present with the band, play occurred more than was expected by chance, and adult males engaged in many of these play bouts. Because the mechanisms driving infanticidal behaviour are not well understood, and adult male coatis show a range of behaviours from infanticide to highly affiliative interactions with juveniles, using coatis as a model system may elucidate mechanisms underlying infanticide.